Trends in the German income distribution: 2005/06 to 2010/11 - Martin Biewen; Martin Ungerer; Max Löffler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
We analyze the potential influence of a number of factors on the distribution of equivalized net incomes in Germany over the period 2005/2006 to 2010/11. While income inequality considerably increased in the years before 2005/2006, this trend was stopped after 2005/2006. Among many other factors, we consider the role of the employment boom and the development of inequality in wage incomes after 2005/2006. Our results suggest that, despite further increases in wage inequality, inequality in equivalized net incomes did not increase further after 2005/2006 because increased within-year employment opportunities compensated otherwise rising inequality in annual labour incomes. On the other hand, income inequality did not fall in a more marked way after 2005/2006 because also the middle and the upper part of the distribution benefitted from the employment boom. Other factors, such as changing household structures, population aging and changes in the tax and transfer system had no important effects on the distribution. Finally, we find little evidence that the distribution of equivalized net incomes was affected in any important way by the financial crisis and the subsequent great recession.
urn:nbn:de:bsz:180-madoc-417917
Keywords: C14; D31; I30; 330; income inequality; poverty